Optimization of Meridional Flow Channel Design of Pump Impeller - Sunao Miyauchi; Hironori Horiguchi; Jun-ichirou Fukutomi; Akihiro Takahashi (International Journal of Rotating Machinery)
The meridional flow channel design of a pump impeller affects its performance. However, since so many design parameters exist, a new design method is proposed in which a meridional and blade-to-blade flow channel is designed by the parallel use of the circulation distribution provided by the designer. Thus, an optimization method was used to design an axis-symmetrical meridional flow channel from the circulation distribution. In addition, the inverse design method proposed by Zangeneh et al. (1996) was employed to design a three-dimensional blade-to-blade flow channel from the circulation distribution and the optimized meridional shape. In this article, a few design examples and these Computational Fluid Dynamics (CFD) validations are also given.